2007
DOI: 10.1002/iroh.200710963
|View full text |Cite
|
Sign up to set email alerts
|

Effects of Daphnia ‐Associated Infochemicals on the Morphology, Polysaccharides Content and PSII‐Efficiency in Scenedesmus obliquus

Abstract: We investigated the effects of infochemicals from Daphnia carinata on the morphology, polysaccharides yield and PSII-efficiency in Scenedesmus obliquus. Infochemicals released from D. carinata induced colony formation in S. obliquus. The contents of soluble extracellular polysaccharides, bounded extracellular polysaccharides, and the total polysaccharides per cell in the induced colonies of S. obliquus increased significantly relative to those of the unicells, which indicated that Daphnia-associated infochemic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
13
0

Year Published

2009
2009
2023
2023

Publication Types

Select...
8

Relationship

5
3

Authors

Journals

citations
Cited by 26 publications
(15 citation statements)
references
References 30 publications
2
13
0
Order By: Relevance
“…Among the molecules found in cell walls (e.g., proteins and lipids), polysaccharides can bind metal ions and protect cells against metal ion toxicity (Bitton and Freihofer ; Cervantes and Gutierrez‐Corona ; Andrade et al ). However, during grazer‐induced colony formation, increase in polysaccharides is also known to affect cell adhesion and contribute to aggregation in algae (Thornton ; Yang et al ). Thus, polysaccharides used for increasing colony size may be inhibited or destroyed by Cu 2+ toxicity, and this effect may account for the decrease in the proportions of big‐sized colonies observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Among the molecules found in cell walls (e.g., proteins and lipids), polysaccharides can bind metal ions and protect cells against metal ion toxicity (Bitton and Freihofer ; Cervantes and Gutierrez‐Corona ; Andrade et al ). However, during grazer‐induced colony formation, increase in polysaccharides is also known to affect cell adhesion and contribute to aggregation in algae (Thornton ; Yang et al ). Thus, polysaccharides used for increasing colony size may be inhibited or destroyed by Cu 2+ toxicity, and this effect may account for the decrease in the proportions of big‐sized colonies observed in the present study.…”
Section: Discussionmentioning
confidence: 99%
“…Moreover, colony formation depends on the species of the grazing zooplankton (Yang et al 2006). Grazers release info-chemicals that stimulate extracellular polysaccharide (EPS) production by Microcystis and subsequent colony formation (Yang et al 2005(Yang et al , 2007. Later studies identified other biotic inducers of Microcystis colonies, such as heterotrophic bacteria (Shen et al 2011), the filamentous cyanobacterium Cylindrospermopsis raciborskii (e Mello et al 2012), and microcystin (Gan et al 2012).…”
Section: Introductionmentioning
confidence: 98%
“…The colony formation of S. obliquus in this study was likely a consequence of increased polysaccharide content in cells, as demonstrated in other studies [16,17]. Moreover, nitrate stress can possibly induce an increase in carbohydrate content [18]; excess carbohydrate is preferentially channeled by algal cells to synthesize high amounts of products, such as polysaccharides [19], thereby contributing to cell aggregation.…”
Section: Resultsmentioning
confidence: 52%